THE BUSINESS OF FOLLOWERS: STUDY OF THE KHALWATIYAH SAMMAN CONGREGATION IN KULO - Sitti Jamilah Amin; An Ras Try Astuti (Dinasti International Journal of Education Management And Social Science, 2021)
This research identifies the business activities related to the teachings of the Khalwatiyah Samman Order which are identical to Sufistic activities. So that it attracts the attention of researchers to find out about the history of the entry of the Khalwatiyah Samman Order, how is the relevance of business activities to the teachings and business activities carried out by followers of the Khalwatiyah Samman Order. This type of research uses a qualitative approach to phenomenology. The results of the study found that the teachings of the Tarekat Khalwatiyah Samman were the teachings of the tarekat which were based on sincerity so that it was solely to Allah swt that their followers cling to it. All teachings and activities, both social and non-social to their economic life, have been arranged in such a way according to their beliefs in carrying out and following these teachings. So that there is no reason for them not to be sincere in living their lives in the world and merely looking for provisions for life in the hereafter by always remembering Allah swt in dhikr